2013
DOI: 10.5455/ijmsph.2013.160420133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of autism spectrum disorders in school-age children in Taif- KSA

Abstract: Background: There has been a reported worldwide increase in the apparent prevalence of autism and related autism spectrum disorders, Such an increase, whether due to an actual increase in incidence of autism or better detection methods. Aims & Objective: To determine the prevalence and describe the clinical characteristics of autism spectrum disorders (ASDs) in school-age children. Material and Methods: The study proceeded in four steps: screening, sampling, and diagnostic assessment. All parents and teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…This low estimate of prevalence in our study is however comparable to several other population‐based prevalence estimates in other Asian countries. In a similar study carried out in TAIF‐KSA (Saudi Arabia) in a school‐going population (7–12 years of age), overall prevalence was very low (0.035%) [Al‐Zahrani, ]. An Indonesian study reported a prevalence of 0.117% for ASD [Wignyosumarto, Mukhlas, & Shirataki, ].…”
Section: Discussionmentioning
confidence: 99%
“…This low estimate of prevalence in our study is however comparable to several other population‐based prevalence estimates in other Asian countries. In a similar study carried out in TAIF‐KSA (Saudi Arabia) in a school‐going population (7–12 years of age), overall prevalence was very low (0.035%) [Al‐Zahrani, ]. An Indonesian study reported a prevalence of 0.117% for ASD [Wignyosumarto, Mukhlas, & Shirataki, ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies of autism frequency have been particularly rare in the Middle East; estimates for ASD prevalence in Saudi Arabia are not available in the literature. 7 Although it is difficult to determine its prevalence rate per country 1 a recent study conducted by Zahrani 2013 8 found that the overall prevalence of autism in the primary school in Taif KSA whose age ranged from 7 to 12 years was 0.035%.…”
mentioning
confidence: 99%
“…The number of children known to have autism has increased dramatically world-wide since the 1980s [2], with an average of 4.3:1 male-to-female ratio [3]. Estimates for ASD prevalence in Saudi Arabia are not available in the literature [4]; however a study conducted by Zahrani 2013 [5] found that the overall prevalence of autism in the primary school in Taif KSA whose age ranged from 7 to 12 years was 0.035%.…”
Section: Introductionmentioning
confidence: 99%